IDENTIFICATION OF IROMP PROTEIN OF K.PNEUMONIAE RESISTANT MUTANTS AGAINST BRL41897 USING SDS –PAGE - Kuswandi, M. (Indonesian Journal of Pharmacy, 2003)
Initial characterization, the MIC, Fe uptake and detection of siderophores, of the resistance K.pneumoniae mutants against BRL41897A (KSL mutants) showed that there were differences amongs them. Therefore it was necessary to observe the OMP and IROMP proteins of the mutants especially which had different MIC’s to the WT galur (M10). Results from SDS-PAGE analysis showed that KSL19 produced 49kDa protein weakly and similar result was found in the 22 kDa protein production by KSL38, KSL52, KSL58 and KSL59. Using Fe-CAA media -media lack of Fe - showed that 3 mutants synthesized certain protein weaker than M10 galur, KSL19 in the production of the 88 kDa protein, KSL38 and KSL59 at the 80 kDa protein. We also observed that KSL19 synthesized new 88 kDa protein. This result showed that certain mutant which had decreased production of one protein could stimulate another weak protein.Key words: SDS-PAGE – IROMP – K.pneumoniae mutants – BRL 41897A.